Oiardubot: uma linguagem de programação especifica para o ensino de robótica com tecnologia livre - Slomski, Gustavo Henrique Beltrani (2021)
Programming is a prerequisite for the development of projects and also a tool of teachinglearning for Arduino platform. However, programming isn’t always an easy task. So, this work aims to develop a domain-specific language to assist in the robotics teaching process. Based on the abstraction of concepts from conventional languages and combined with a simple syntax in portuguese, this tool brings innovation and assistance to the teaching of robotics. Through the construction of a metamodel, combined with the resolution of a grammar, inserted in an integrated development environment, it was possible to develop a domain-specific language. The proposed language aims to act in the middle of the block language and the conventional Arduino language, in order to contribute and assist in the teaching-learning process of educational robot programming. Thus, through a web editor, you can program a pseudocode entirely in Portuguese and, jointly, perform the translation to the conventional language of Arduino, being instantly ready for the application.